Choroidal thickness in patients with progressive and stabilized POAG (Ukrainian Journal of Ophthalmology, 2026)
Purpose: To investigate choroidal thickness in patients with progressive and stabilized primary open-angle glaucoma (POAG).Materials and Methods: Forty-nine patients (87 eyes; age, 52 to 77 years) with stage 1, 2 or 3 POAG were involved in the study. Choroidal thickness was measured with optical coherence tomography.Results: The foveal choroidal thickness and peripapillary choroidal thickness were thinner in progressive POAG versus stabilized glaucoma (184.2±20.6 µm vs 261.1±19.4 µm, p0.05, respectively). Foveal choroidal thickness was directly correlated with ganglion cell complex thickness (r=0.5725, p < 0.05), and negatively correlated with progressive POAG (r=-0.4246, p < 0.05).Conclusion: In patients with POAG, foveal choroidal thickness is directly correlated with ganglion cell complex thickness and disease progression. The foveal choroidal thickness and peripapillary choroidal thickness were 31% and 23%, respectively, thinner in progressive POAG versus stabilized POAG.
Keywords: progressive and stabilized POAG; choroidal thickness